Film Dokumenter Pendek Sebagai Media Promosi Ekowisata Mangrove Blok Bedul di Desa Sumberasri Banyuwangi - Mecha, I Putu Sudhyana; Indriani, Indriani; Febrian, Ayu Wanda (Sekolah Vokasi, Universitas Gadjah Mada, 2022)
The development of promotion media creates a flow of media innovation by utilizing technology and the internet. The use of the internet's position as a communication channel can provide information to potential tourists. Like any ecotourism promotion activity that needs to be completed with film screenings or presentations on the quality of ecotourism products, in which research in the form of a short documentary film as promotion media for Mangrove Blok Bedul Ecotourism is one of solution to the problems related about promotion. The research method used in this study is a qualitative approach which research is carried out in natural conditions. Data collection method used are interviews, observation, questionnaires and documentation. The analysis technique includes data reduction, data display and conclusions made simultaneously until the data obtained is valid. The purpose of this study are to find out the potential of Mangrove Blok Bedul Ecotourism in Sumberasri village then it can be as a storyline of short documentary film. Furthermore knowing the pre-production, production and post-production processes of designing short documentary film. In additional, the results obtained are knowing the efforts to publish short documentary film that have been made by researcher through YouTube social media.